FL Borneo Store / Lyn Palrick and Fatin Nursyuhada Azlin - Palrick, Lyn; Azlin, Fatin Nursyuhada (2022)
One of the most wanted entrepreneur goals is achieving a successful business in the future. To gain success in the business does not only depends on what you have, but also on what you learn. Not only that, but hard work is also one of the keys on how an entrepreneur can achieve their goal. Since everything is at our fingertips, online platform is now a leading way to start a business by the new and old entrepreneur outsides. It is a very convenient way of shopping, and everyone is slowly turning into it in this era. It only took us a second to make use of this opportunity to build a stable business via online platform alongside building a loyal customer base before deciding on expanding it even further. FL Borneo Store is an online business that focuses on promoting Sarawak’s most sought-after fabric and handmade crochet items. Since both are a ‘hard-to-find’ items, we decided to take the risk to become an agent as fabric resellers and crocheting products which requires a lot of process and time consuming. Both products have their own speciality and benefits to users. We aim to promote happiness through our products by ensuring its’ quality and guaranteed fast delivery, right at their doorstep. FL stands for Fatin and Lyn, which is adapted from their name initial letter. As for the name ‘Borneo store’, the idea comes from the fact that we are both Sarawakian people. We focus on promoting our products through social media platform. We choose Facebook for it is a low-cost marketing approach especially for a small business that had just started. Due to limited business budget, we decided to cut cost by turning to online platform and make use of word-of-mouth marketing. Since we are still in the recovery phase from this endemic, a vast majority of people opt for online shopping. We make use of this situation to attract potential customers through social media by posting aesthetic and eye-catchy posts regarding our products. By having a goal to achieve, mission and vision, it gives us motivation and determination to achieve our goals of becoming a successful entrepreneur with a wellknown online business platform in the future. Last and not least, we believe that our Batik products will benefit both gender and people of different age groups. It is a pride symbol for Borneo people, and we would like to share the uniqueness to other people as well. As for the crochet items, it is a handmade item with love in which we are aiming to put a smile on people’s face. We prioritise more in spreading happiness, which is why our items are all set affordable for all. Despite being a student, that does not hinder us from starting our own business journey and making our dream into reality.